На пути к оптимальному структурированию системы видовых парадигм в русском языке - Klimonov, Vladimir (Studia Rossica Posnaniensia, 2022)
The author of this paper defines the aspectual paradigms of Russian verbs as such grammatical structures whose formal aspect is correlated with the conceptual one, therefore being its cognitive counterpart. With a view to analysing these paradigms he uses the theory of markedness as an analytic tool. According to it, the grammatical changes that occur in natural languages originate from general principles of naturalness which are typologically relevant. They result in morphological shifts that are linked to the verbalisation of Russian aspectual paradigms and allow to predict the direction of their development. In particular, the principle of natural grammatical development should be considered crucial. It means that the grammatical changes in natural languages cause elimination of marked elements, so that these more complex linguistic structues are replaced with less complex ones. Such a principle manifests an unconscious desire of language users to minimise their linguistic efforts, as it would place an additional burden on interpersonal communication.